2006
DOI: 10.1148/radiol.2411050928
|View full text |Cite
|
Sign up to set email alerts
|

Usual Interstitial Pneumonia and Chronic Idiopathic Interstitial Pneumonia: Analysis of CT Appearance in 92 Patients

Abstract: UIP has a characteristic appearance that usually facilitates distinction from other types of chronic IIPs at thin-section CT. The most useful finding when differentiating UIP from NSIP was the extent of honeycombing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 35 publications
6
42
1
2
Order By: Relevance
“…In a separate study designed to distinguish UIP from NSIP Akira et al [21] found traction bronchiectasis was significantly more common in UIP (and by extension was likely to be associated with a worse outcome). Conversely, in a third study (n=72), Sumikawa et al [20] did not find traction bronchiectasis scores aided differentiation between fibrotic NSIP and UIP. These studies estimated the severity of traction bronchiectasis using similar methodologies: (1) by counting the number of pulmonary segments in which it was present and (2) by assigning a score according to the anatomical level at which dilatation was identified (peripheral airway dilatation was assigned a lower score than proximal dilatation) [13,20].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a separate study designed to distinguish UIP from NSIP Akira et al [21] found traction bronchiectasis was significantly more common in UIP (and by extension was likely to be associated with a worse outcome). Conversely, in a third study (n=72), Sumikawa et al [20] did not find traction bronchiectasis scores aided differentiation between fibrotic NSIP and UIP. These studies estimated the severity of traction bronchiectasis using similar methodologies: (1) by counting the number of pulmonary segments in which it was present and (2) by assigning a score according to the anatomical level at which dilatation was identified (peripheral airway dilatation was assigned a lower score than proximal dilatation) [13,20].…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, in a third study (n=72), Sumikawa et al [20] did not find traction bronchiectasis scores aided differentiation between fibrotic NSIP and UIP. These studies estimated the severity of traction bronchiectasis using similar methodologies: (1) by counting the number of pulmonary segments in which it was present and (2) by assigning a score according to the anatomical level at which dilatation was identified (peripheral airway dilatation was assigned a lower score than proximal dilatation) [13,20]. However, these scoring systems are dependent upon the extent and distribution of fibrosis and may not necessarily reflect the intensity of local architectural distortion.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…(29)(30)(31)(32)(33)(34) In contrast, extensive honeycombing is much more commonly a manifestation of UIP. (35) The findings described above for NSIP are not specific. Therefore, in the absence of a definable collagen vascular disease or exposure to fibrogenic drugs, surgical lung biopsy is necessary.…”
Section: Pattern 2 Nodulesmentioning
confidence: 85%
“…17,19,[23][24][25][26] In our study, the T group more often demonstrated the typical axial distribution of UIP than did the major allele group; this likely led to a higher percentage of UIP and probable UIP scores in these subjects than in those in the G group. We theorize that subjects who carry the minor T allele at the rs35705950 SNP, and then develop pulmonary fibrosis, are more likely to develop the typical imaging manifestations of UIP/IPF.…”
Section: Discussionmentioning
confidence: 96%